Atividades experimentais em aulas de física: repercussões na motivação dos estudantes, na dialogia e nos processos de modelagem - Francisco Pazzini Couto (2009)
Experimental activities have an unexpected role in Physics education, promoting the debate about its importance or not to contribute to conceptual and procedural learning. The present research followed for a few months two Physics teachers that have been detached in their schools for their recognized work based on experimental Physics teaching. The teachers used experimental activities to promote science learning in different scholar conditions.The aim of this study is to examine the efficiency of experimental activities in three complementary directions. In the first one, we examined the utterance strategies used by the teachers during experimental activities, in order to verify if such strategies promote dialogic discourse and increase the quality of students. participation. In the second direction, we sought evidences that the use of experiments increase the interest and engagement of the students in Physics class and which teaching strategies were used with the purpose of sustaining such engagement. In the third direction, we verified if the experimental activities fulfil the function of mediating the relations between the word of object and phenomena with the word of models and Physics theories, searching for evidences that such activities provides elements for the students to participate in construction and validation of Physics models.For that, we used a socio-cultural approach based on Vygotsky, Bakhtin and Wertsch. The data were built by means of interviews, questionnaires and selected teaching episodes from recorded lessons and field notes. We found that in different settings, with different material support and pressures from curricula, the teachers accomplished to use experimental activities as means to present, exemplify and examine Physics concepts. We conclude that in both studied environments the experimental activities contribute to the interest and greater participation of the students in the Physics class, besides supporting the process of construction and validation of Physics models. On the other hand, against the odds, even in experimental activities in which there are problems, discussion and interpretation of results, the dialogic communicative approach were rarely present.